Identification of subgingival periodontopathogen in subjects with chronic periodontitis - Kamil, Wisam Alaa; Al-Bayati, Lina Hilal Abbood; Muhammad Ali, Suhaila; Arief Ichwan, Solachuddin Jauhari; Phang, Ing Chia; Zainal Abidin, Zamirah; Mohd Said, Shahida (Elsevier, 2019)
Objective: The aim of this study was to identify the presence of subgingival periodontopathogen in subjects diagnosed with chronic periodontitis among patients attending International Islamic University Malaysia, Kulliyyah of Dentistry Polyclinic, Kuantan, State of Pahang. Materials and Methods: Fifty systemically healthy Malaysian subjects were enrolled in this study. Thirty of those who diagnosed with chronic periodontitis were recruited for the test group, and 20 subjects were considered the control group based on the absence of clinical attachment loss. The clinical periodontal parameters including full mouth plaque scores, bleeding on probing, pocket depth and clinical attachment loss were recorded. Subgingival plaque samples were collected using periodontal curette from deep pockets of each individual and pooled for analysis and DNA extraction. The presence of Porphyromonas gingivalis (Pg) was assessed by polymerase chain reaction. Result: There was highly significant difference between both groups in respect to the clinical periodontal parameters (p < 0.001). The prevalence of Pg was 66 % in the study sample with significant increase (p=0.002) in the test group 83.33 % compared to control 40%. Among the chronic periodontitis subjects, the presence of Pg is associated with the increased probing pocket depth (p=0.007). Conclusion: The presence of Pg is significantly detected in chronic periodontitis compared to individuals without periodontal destruction.